Quality Assurance: Studi Kasus Di Universitas Pasifik Morotai Maluku Utara - Irawati Sabban; Abdul Aziz Wahab; Danny Meirawan; Endang Herawan; Yayah Huliatunisa (Jurnal Administrasi Pendidikan, 2022)
This study aims to evaluate the implementation of internal quality assurance at Pacific Morotai University and provide detailed findings regarding the constraints faced by the Pacific Morotai University Quality Assurance Institute (LPM), North Maluku. The approach used in this study is a qualitative approach with a case study method at the Pacific University of Morotai, North Maluku; Data was collected based on document search, observation, and interviews. The results of the study show that the implementation of internal quality assurance at Pacific Morotai University faces the problem of a lack of auditors who have an understanding and a number of human resources in carrying out monitoring and evaluation tasks. The technical implementing unit formed by LPM in carrying out its duties only consists of six people spread across six faculties with details of one person for each faculty. The impact is due to the lack of auditors who are experts in quality assurance, so that it has an impact on quality assurance or external accreditation. In fact, the university does not yet have institutional accreditation status and eleven study programs have the same accreditation rating, namely C. Thus, the implementation of quality assurance is not carried out optimally and properly monitored, making it difficult to measure university quality achievements in setting higher education standards.